BENOSIN: Bread Waste Bioethanol Conversion Unit as an Innovation in Bioethanol Production Using Apple Peels to Achieve a Sustainable Green Economy - Khansa Praningdita Sulistyo; Firda Cahya Salbina; Azelia Anisa Rahma (TEKNIK, 2025)
Currently, fuel oil is a primary natural resource in the transport sector. However, the availability of fossil fuels is shrinking while the demand for fuel is rising. Expired bread is not worthy of consumption and is often discarded without being used as something more economical and environmentally friendly.   Therefore, the study aims to convert bread waste into bioethanol (C2H5OH) as a gasoline mixture that can reduce emissions of pollutants such as carbon monoxide (CO) and potentially improve air quality. These bioethanol products will create energy security, reducing dependence on a single energy source.   Bread waste serves as a substrate with an apple peel catalyst. This method of making bioethanol is through fermentation assisted by Saccharomyces cerevisiae with the addition of urea fertilizer as a nutrient. The multistage distillation column is equipped with hydrophobic material to help the separation process. The results of this study show that bioethanol from expired bread waste is worthy of being used as a gasoline mixture for motor vehicle fuel. The ethanol produced is directly proportional to the amount of bread waste, but there is still a maximum limit. The time variations used are 24 hours, 48 hours, and 72 hours.   Based on this study, the optimal condition of Saccharomyces cerevisiae works at a temperature range of 30-35°C with a pH of 4-6.